Back Cover: Synthetically Tuning the 2‐Position of Halogenated Quinolines: Optimizing Antibacterial and Biofilm Eradication Activities via Alkylation and Reductive Amination Pathways (Chem. Eur. J. 27/2016). Issue 27 (23rd May 2016) - Basak, Akash; Abouelhassan, Yasmeen; Norwood, Verrill M.; Bai, Fang; Nguyen, Minh Thu; Jin, Shouguang; Huigens, Robert W.
Abstract : The 2‐position of the halogenated quinoline (HQ) scaffold can be dramatically tuned through diverse and practical synthetic pathways, including reductive amination and alkylation reactions. New HQs discovered during these investigations potently eradicate methicillin‐resistant Staphylococcus aureus (MRSA), methicillin‐resistant Staphylococcus epidermidis (MRSE) and vancomycin‐resistant Enterococcus faecium (VRE) biofilms, which display high levels of tolerance towards conventional antibiotic therapies. The background image is reproduced with permission and copyright of the British Editorial Society of Bone and Joint Surgery ( Bone Joint J .2013, 95B, 678–682; Figure 2 b). More information can be found in the Full Paper by R. W. Huigens III et al. onpage 9181 ff.